Asiatic Acid Inhibits OVX-Induced Osteoporosis and Osteoclastogenesis Via Regulating RANKL-Mediated NF-κb and Nfatc1 Signaling Pathways - Hong, Guoju; Zhou, Lin; Han, Xiaorui; Sun, Ping; Chen, Zhenqiu; He, Wei; Tickner, Jennifer; Chen, Leilei; Shi, Xuguang; Xu, Jiake (Frontiers in Pharmacology, 2020)
Asiatic acid is a natural triterpenoid compound extracted from the plant Centella asiatica. It has been used as a highly efficient compound for the treatment of cancer and hyperlipidemia, as well as possessing potential anti-inflammatory properties. However, its effects on bone metabolism and osteoporosis remain unknown. The aims of this study were to investigate the effects of Asiatic acid on osteoclasts, and the underlying molecular mechanisms regulating its effects on RANKL-induced signaling pathways. We found that Asiatic acid inhibited multinucleated tartrate-resistant acid phosphatase (TRAcP) positive osteoclast formation and bone resorption in a dose dependent manner. Real time PCR showed that Asiatic acid reduced the expression of osteoclast related target genes including Ctsk, Nfatc1, Calcr, and Atp6v0d2. Western blot and luciferase reporter gene assays revealed that Asiatic acid inhibits RANKL-activated NF-κB and NFATc1 signaling pathways. Further, in vivo study demonstrated that Asiatic acid attenuates estrogen deficiency-induced bone loss in ovariectomized mice. MicroCT and histology analyses revealed that osteoclast numbers were significantly suppressed in Asiatic acid treated groups. Furthermore, serum levels of TRAcP and CTX-1 were downregulated in treated groups. Taken together, our data show that Asiatic acid can inhibit osteoclastogenesis and reduce OVX-induced bone loss through RANKL-mediated NF-κB and NFATc1 signaling pathways, suggesting that Asiatic acid may be a potential and effective natural compound for the treatment of excessive osteoclast-related diseases such as osteoporosis.